2022
DOI: 10.1177/00315125221125608
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Inversion Proprioception Impairment in Persons with Chronic Ankle Instability Is Task-Specific

Abstract: While investigators have often compared ankle proprioception between groups with and without chronic ankle instability (CAI), findings have been inconsistent. Possibly this is because ankle proprioceptive impairment in this population is task-specific. Thus, we aimed to compare ankle inversion proprioception in individuals with and without CAI in two task conditions: (i) when standing (not challenging) and (ii) when on a step-down landing (minimally-challenging). Ankle inversion proprioception was measured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
3
5
0
Order By: Relevance
“…Only when the testing value is changed above the MDC value can the change value be considered as the effect of treatment or intervention (Portney, 2020). In the current study, the AIDAW MDC 90 values were similar to those of the AIDAL method (0.04 for both the CAI group and the non-CAI groups) (Han et al, 2021). These results suggest that the measurement error was small and that when the AIDAW is used as an evaluation tool for rehabilitation of ankle proprioception, an improvement of the AIDAW proprioceptive score greater than 0.04 can be considered as true change.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Only when the testing value is changed above the MDC value can the change value be considered as the effect of treatment or intervention (Portney, 2020). In the current study, the AIDAW MDC 90 values were similar to those of the AIDAL method (0.04 for both the CAI group and the non-CAI groups) (Han et al, 2021). These results suggest that the measurement error was small and that when the AIDAW is used as an evaluation tool for rehabilitation of ankle proprioception, an improvement of the AIDAW proprioceptive score greater than 0.04 can be considered as true change.…”
Section: Discussionsupporting
confidence: 74%
“…Previous research has reported comparable test-retest reliability for movement discrimination assessment devices. Specifically, the ICC values were 0.70-0.80 for CAI and non-CAI groups tested using the AIDAL (Han et al, 2021), and ICC values were 0.70-0.88 for the young and elderly groups when assessing their postural sway movement discrimination sensitivity using the Sway discrimination apparatus (SwayDA) (Chen et al, 2019). Therefore, this novel AIDAW method can be considered to be reliable for assessing ankle proprioception during walking in individuals with and without CAI.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations